2012
DOI: 10.1038/ijo.2012.108
|View full text |Cite
|
Sign up to set email alerts
|

Enuresis—an unattended comorbidity of childhood obesity

Abstract: Obese children are at increased risk for enuresis. Enuresis should be clarified during the primary workup of every obese child and adolescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
41
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 34 publications
(64 reference statements)
8
41
3
4
Order By: Relevance
“…Thus, NE prevalence varies markedly among countries and regions within countries, reflecting socioeconomic differences, educational levels, heredity factors, and inclusion criteria. Consistent with most studies, overall prevalence was greater in boys [2,6,12,13,19], about a quarter of cases were SNE, and prevalence decreased with age. It is critical to identify underlying correlative secondary diseases, such as phimosis, urinary tract infection, spina bifida occulta (SBO), and psychological stressors.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Thus, NE prevalence varies markedly among countries and regions within countries, reflecting socioeconomic differences, educational levels, heredity factors, and inclusion criteria. Consistent with most studies, overall prevalence was greater in boys [2,6,12,13,19], about a quarter of cases were SNE, and prevalence decreased with age. It is critical to identify underlying correlative secondary diseases, such as phimosis, urinary tract infection, spina bifida occulta (SBO), and psychological stressors.…”
Section: Discussionsupporting
confidence: 70%
“…It was reported that male gender, younger age, daytime incontinence, deeper sleep, positive family history of NE, attention deficit/hyperactivity disorder (ADHD), and constipation may also increase the NE risk [3,12,23], and our study indicated that a positive family history, SDB, constipation, male gender and age can significantly increase the NE risk.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…13 A survey of children in the United States, reported higher prevalence rates of 33% at 5 years, 18% at 8 years, 7% at 11 years, and 0.7%at 17 years. 14 Other research show reduced rates of enuresis; Weintraub and her colleagues use data showing that at the age of 5 years, just 3-7% are experiencing enuresis and this reduces significantly as age progress 15 .…”
Section: Enuresis: a Common Issue Among Children And Adolescentsmentioning
confidence: 99%
“…(20) tarafından 2013 yılında yapılan bir çalışmada; obezlerin, normal kilolu çocuklara oranla daha fazla enürezis yakınması olduğu bildirilmiştir. Monosemptomatik EN ve işeme disfonksiyonu bulunan 250 hastanın tedaviye yanıtlarının değerlendirildiği bir başka çalışmada, hastaların yarısının aşırı kilolu ve obez olduğunu ve fazla kilo ile tedaviye yanıt arasında ters bir orantı olduğu belirtilmiştir (21).…”
unclassified